The Significance of ‘The’ for the fundamentalists: A Linguistic Study (Journal of the College of Basic Education, 2022)
The research is an attempt to emphasize the mutual views between the fundamentalists and linguists in the field of semantic study, representing by the significance of ‘The’(The first two letters in Arabic alphabetic) . The reliance will be on the valuable sources of fundamentalists which enrich the spirit of the language. The research summarize what did the scientists of the fundamentalism expose concerning the significance of ‘The’. They are considered the most obscure letters that require a study for their meaning. The research does not only give the meaning of these letters but also determine the nouns with which these letters they could be used as with absorption and gender. The research also takes a close look at the clues that have a great impact on the meanings of ‘The’ and to prove one or to exclude or to prefer one on the other. This what fundamentalists are still taking in the account and deal with as the core and the focus